RANCANG BANGUN SISTEM INFORMASI E-SURAT PEMBERITAHUAN DIMULAINYA PENYIDIKAN PADA SATUAN RESERSE NARKOBA PALEMBANG BERBASIS WEB - Haryadi, Ahmad Puput; Damayanti, Nita Rosa (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2023)
The Palembang Polrestabes does not yet have a system for inputting data to prepare and send a Notice of Commencement of Investigation (SPDP) so that the process is slow in managing the file. This research aims to build E-Letter Notification System for the Start of Investigations (E-SPDP) at the Palembang Police Narcotics Unit Web-Based to make it easier for Administrative Officers to complete so that the information obtained is valid, effective and efficient. SPDP is submitted by the investigator to the public prosecutor in order to guarantee the implementation of the case oversight function owned by the Public Prosecutor. Through Decision Number 130/PUUXIII/2015 the Constitutional Court is conditionally unconstitutional that the SPDP must be submitted to the Public Prosecutor, the reported party and the victim/reporter no later than seven days after the investigation warrant was issued. The research method used is Rapid Application Development (RAD) a model of the development cycle with a short emphasis on additional software development, although the development process is short, it does not reduce the quality of the product. The final result of this research is the creation of a webset that can facilitate data processing, data storage, data search, letter creation and report generation with a web-based information system